Suppression of Nonlinear XPM Phenomenon by Selection of Appropriate Transmit Power Levels in the DWDM System - Tomáš Ivaniga; Petr Ivaniga (International Journal of Optics)
In the 21st century, it is not possible to implement fully optical communication systems without software tools to test the system for all unwanted phenomena occurring during real-time operation. With ever-increasing transmission rate and low latency, nonlinear phenomena are associated with higher power levels and smaller spacing between channels began to appear in OFs (optical fibers). This paper aims to implement a four-channel DWDM (Dense Wavelength Division Multiplex) system on which the nonlinear XPM (cross-phase modulation) phenomenon will be investigated. At the output of the system, we will eliminate the phenomenon (partially suppressed) by the appropriate choice of transmitting power levels (power levels operating at 193,025 THz to 193,175 THz) when the OF is dispersed. In optical transfer data systems a system is functioning if the measured BER parameter is not bigger than 10−12.